Retromolar intubation for the general anesthesia of maxillofacial fracture patients - Xiaorong Tang; Lili Ding; Yitao Li (BMC, 2024)
Abstract Background Evaluate the possibility of retromolar intubation for general anesthesia in patients with maxillofacial fractures. Methods The medical records of 54 patients with maxillofacial fractures who visited the Oral and Maxillofacial Surgery Department of Nantong First People's Hospital from January 2020 to August 2022 were collected. The retromolar areas of each patient were measured from the coronal CT images, and correlated with the patient's age, sex, type of fracture (i.e., maxillary fracture, mandibular fracture, or complex fracture of multiple maxillofacial bones), and the presence of the third molar (verified from 3D CT). The dimensions of the retromolar areas were finally compared with the outer diameter (OD) of standard endotracheal tubes (ETTs), most importantly the size 7.5 ETT (OD 10.3 mm) for male and the size 7.0 ETT (OD 9.8 mm) for female. Results The survey included 38 male and 16 female patients, with an average age of 44.1 and 54.3 years, respectively. The dimensions of the retromolar area (height × width) were as follows: male, (9.39 ± 1.77) mm × (12.08 ± 0.98) mm on the left and (9.81 ± 2.23) mm × (11.77 ± 1.08) mm on the right; female, (8.82 ± 1.53) mm × (10.51 ± 1.00) mm on the left and (9.73 ± 1.60) mm × (10.63 ± 1.58) mm on the right. The width was always larger than the OD of the routinely used ETT, but the height could be smaller by less than 1 mm. However, the oral mucosa can be compressed to allow the ETT to fit in the retromolar area. Conclusions The retromolar area provided appropriate space to place a reinforced ETT for patients with maxillofacial fractures needing general anesthesia that must not interfere with intermaxillary ligation. Retromolar intubation can help maxillofacial fracture surgeries that focus on occlusal restoration.